Do Ethical Climate Have Impact on Job Satisfaction of Staff in West Sulawesi Hospital, Indonesia? - Lalu Mumahammad Saleh; Eka Fatmawati; Indah Nur Insani; Andi Indahwaty Sidin (Media Kesehatan Masyarakat Indonesia, 2021)
A positive ethical climate can create job satisfaction for employees. This study aims to see the effect of ethical climate on the job crafting of health workers and its impact on job satisfaction. This research is a quantitative study with a cross-sectional study approach. The population consisted of health workers at RSUD Mamuju, RS Bhayangkara Polda Mamuju and RS Mitra Manakarra Mamuju, West Sulawesi Province with 155 employees selected as samples. Samples were selected by quota sampling, then analyzed using the Path Analysis test at SPSS 20. The value of standardized coefficients beta as a direct effect is 0.023 and the indirect effect is 0.043, meaning that the value of the indirect effect is greater than the value of the direct effect. These results indicate that indirectly the Ethical Climate (EC) through Job Crafting (JC) has a significant impact on Job Satisfaction (JS). Thus, "there is an effect of EC (X) through JC (Y) on JS (Z)". JC mediates EC in improving employee JS. Job crafting can affect job satisfaction if hospital staff have another supporting factor, namely the ethical climate. To improve the ethical climate by providing a motivational boost, management must identify the dimensions of employee work activities in job crafting, apart from training and feedback from direct superiors.